The Impact of Ambiguity on Managerial Investment and Cash Holdings. (1st August 2014) - Neamtiu, Monica; Shroff, Nemit; White, Hal D.; Williams, Christopher D.
Abstract Standard finance theory suggests that managers invest in projects that, in expectation, produce returns that justify the use of capital. An underlying assumption is that managers have the information necessary to understand the distributional properties of the pay‐offs underlying the decision. This paper examines firm investment behavior when managers are likely to find it more challenging to develop expectations of pay‐offs, namely during periods of increased macroeconomic ambiguity. In particular, we examine how macroeconomic ambiguity – proxied by the variance premium (Drechsler, 2010) and the dispersion in forecasts of corporate profits from the Survey of Professional Forecasters (Anderson et al., 2009) – impacts managerial capital investment and cash holdings. Consistent with ambiguity theory, we find that macroeconomic ambiguity is negatively associated with capital investment and positively associated with cash holdings. These results are robust to alternative explanations related to risk, investor sentiment and economic conditions. Moreover, consistent with recent theoretical real options literature, we find that ambiguity reduces the value of investment opportunities, while risk increases the value of such opportunities. Overall, these findings provide initial empirical evidence on the economic distinction between ambiguity and risk with respect to managerial investment and cash holdings.